CoP Nanoparticle Confined in P, N Co‐Doped Porous Carbon Anchored on P‐Doped Carbonized Wood Fibers with Tailored Electronic Structure for Efficient Urea Electro‐Oxidation. Issue 24 (13th May 2022) - Kang, Jingfei; Yang, Fan; Sheng, Can; Xu, Han; Wang, Jiayi; Qing, Yan; Wu, Yiqiang; Lu, Xihong
Abstract: Electronic structure optimization and architecture modulation are widely regarded as rational strategies to enhance the electrocatalysts catalytic performance. Herein, a hybridization of ZIF‐67‐derived CoP nanoparticles embedded in P, N co‐doped carbon matrix (PNC) and anchored on P‐doped carbonized wood fibers (PCWF) is constructed using a simple simultaneous phosphorization and carbonization strategy. Benefiting from the optimized surface/interface electronic structures, abundant exposed active sites, and outstanding conductivity, the CoP@PNC/PCWF can drive the urea oxidation reaction (UOR) with greater activity and better stability than most recently reported electrocatalysts, in which a potential as low as 1.32 V (vs reversible hydrogen electrode, RHE) is needed to reach 50 mA cm ‐2 and shows excellent durability. Furthermore, for overall urea splitting, using the CoP@PNC/PCWF electrocatalyst as the anode and commercial Pt/C supported on nickel foam as the cathode, an ultralow cell voltage of 1.50 V (vs RHE) is expected to achieve the 50 mA cm ‐2 and operate continuously for more than 50 h at 20 mA cm ‐2 . The reported strategy may shed light on the use of renewable resources to design and synthesize high‐performance non‐Ni‐based phosphides UOR electrocatalysts for energy‐saving H2 production. Abstract : A simple simultaneous phosphorization and carbonization strategy is developed to synthesize CoP@PNC/PCWF. The well‐defined CoP@PNC/PCWF can effectively ensure the uniform distribution of CoP nanoparticles, and P doped into carbon matrix can induce more defects in carbon, and improve the electronic interaction between CoP and PNC. Hence, the CoP@PNC/PCWF shows superior electrocatalytic UOR performance in alkaline medium.